PERENCANAAN PENGEMBANGAN ARSITEKTUR SISTEM INFORMASI PERGURUAN TINGGI MENGGUNAKAN METODE ENTERPRISE UNIFIED PROCESS (EUP) (STUDI KASUS : STMIK CIC CIREBON) - Sokibi, Petrus; Adnyana, I Ketut Widhi (LPPM STMIK STIKOM Indonesia, 2018)
Enterprise Unified Process (EUP) as one of the methods or terms of reference for building an information architecture is a development cycle of Information Technology (IT) extension of the Rational Unified Process (RUP). RUP defines a software development cycle. While EUP not only handles the software development cycle but covers the entire life cycle of IT and adds enterprise management disciplines with cross-system to the needs of an enterprise architecture. The study produced a blueprint consisting of arsitetur business, data architecture, application architecture and technology architecture based strategic reusable. In addition, resulting from the integration of the four architecture. Keywords: enterprise architecture, Enterprise Unified Process (EUP), blueprint, reusable